2022
DOI: 10.17507/jltr.1304.10
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Learning Method Through Smartphone Assistance in Promoting Speaking Ability

Abstract: Self-regulated learning is a method of the student-centered learning paradigm. This method encourages students to be actively involved in the learning process, organize themselves, recognize their capabilities, and take the initiative to decide the appropriate way to achieve the learning achievement. The use of self-regulated learning with smartphones' assistance has had a double effect on students' language proficiency. However, the self-regulated learning method with smartphone assistance in the speaking cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This study investigates the crucial role of self-regulated learning (SRL) in enhancing students' English language acquisition. SRL involves strategies like setting effective study schedules, managing the learning environment, overcoming procrastination, and recognizing how cell phones can support learning goals (Eissa, 2020;Khiat & Vogel, 2022;Menggo et al, 2022;Gonzalez-DeHass, 2019;Domínguez & García, 2017;Zimmerman, 2001). Within the English as a Foreign Language (EFL) context, SRL promotes strong resource management, motivation, persistence, and commitment -all critical drivers of language learning success.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…This study investigates the crucial role of self-regulated learning (SRL) in enhancing students' English language acquisition. SRL involves strategies like setting effective study schedules, managing the learning environment, overcoming procrastination, and recognizing how cell phones can support learning goals (Eissa, 2020;Khiat & Vogel, 2022;Menggo et al, 2022;Gonzalez-DeHass, 2019;Domínguez & García, 2017;Zimmerman, 2001). Within the English as a Foreign Language (EFL) context, SRL promotes strong resource management, motivation, persistence, and commitment -all critical drivers of language learning success.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…The evaluation is in the form of scores and markers of errors or inaccuracies when speaking, such as the five basic components of speaking. Menggo et al [19] found that smartphone-assisted independent learning had a positive effect on improving speaking skills. This article presents the results of observations through a questionnaire according to the perceptions of PBSI students of Universitas Tidar regarding the need for speaking learning media.…”
Section: Introductionmentioning
confidence: 99%
“…SRL also can be recognized as an active, beneficial process in which learners set learning goals and then monitor, regulate, and manage their cognition, motivation, and behavior (Paul R. Pintrich, 2000;Zimmerman, 2008). Moreover, Menggo et al (2022) assert that SRL is an educational process that enables students to self-regulate when determining ideas or concepts and evolving their learning strategies to accomplish attainable outcomes. Unlike conventional education, these learning strategies concentrate on students' interests and acknowledge students' voices as the basis of the learning experience (Alten et al, 2020;Nen et al, 2022;Olubode et al, 2022).…”
Section: Introductionmentioning
confidence: 99%